Fisher-foragers Amidst the Reeds: Loptuq Perception of Waterscapes in the Lower Tarim Area - Svanberg, Ingvar; Ståhlberg, Sabira (Ethnobiology Letters, 2020)
Toponyms and hydronyms encode important information about human perceptions of the environment in a specific context. This article discusses the Loptuq, a group of Turkic-speakers, who until the 1950s lived as fishers-foragers at the Lower Tarim River, Eastern Turkestan (contemporary Xinjiang, China), and their use of common reed (Phragmites australis) as an example for the close connection between language, culture, social relations, economic activities, and human perceptions about the surrounding environment. Operating in lakes and swamps for their economic activities (fishing, hunting, foraging, and occasional transport), exploring and observing vegetation and animal life, the Loptuq developed and transmitted information through naming their habitat. Today both their habitat and the earlier knowledge have disappeared, but the perceptions and uses of resources can at least partly be reconstructed through foreign explorers’ narratives and field notes.